Lightweight recycled gypsum with residues of expanded polystyrene and cellulose fiber to improve thermal properties of gypsum - de Oliveira, K. A. [UNESP]; Oliveira, C. A.B. [UNESP]; Molina, J. C. [UNESP] (Editorial CSIC, 2021)
In this study, different proportions of gypsum composite reinforced with recycled cellulose fibers and expanded polystyrene were produced to study the properties of thermal conductivity, density, and flexural strength to be used as sealing plates to improve the thermal comfort of buildings. Different gypsum matrix composites were produced with varied proportions of cellulose fiber and expanded polystyrene, to analyze the influence of residues on the properties of the material. The thermal conductivity obtained for composites with greater amounts of expanded polystyrene was 0.18 W/mK, a 48% reduction in relation to plasterboard, improving thermal performance. The flexural strength was also analyzed, which met the minimum strength requirement for use as gypsum composites, however, it is not enough to be used in places that require mechanical resistance, thus it is indicated for sealing plates applications, improving the thermal performance of places where only plasterboard is used.
Keywords: Cellulose fiber; Composites; Expanded polystyrene; Gypsum; Thermal insulation